Health and social informatics and service design competences - Teachers’ of university of applied sciences view of common competence - Ahonen, Outi Maria; Kinnunen, Ulla-Mari; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2020)
The purpose of the study was to find out teachers’ views of the assessment tool, which has been developed for the students in relation to the assessment of competence in the development of services in health and social care. A previously developed competence assessment tool based on the international curriculum for informatics in health and social care and the descriptions of service design at the European Qualifications Framework level (EQF) for students of the university of applied sciences was tested and validated. A multidisciplinary group of teachers (N = 73) from the national project participated in three (n = 23; 25; 20) Delphi rounds. Teachers evaluated the importance of teaching the subject matter and the suitability of the statement to assess the student’s content competencies. A four-point Likert scale (not important - important and not suitable – suitable) was used to assess the importance and suitability. The reliability of the content validity index (S-CVI / Ave) and the item level content validity index (I-CVI), which were defined as 0.80, were calculated. After the evaluation, 40 competence sentences were formed to describe the common skills required by students for the development and use of digital services in health and social care. The results show that teachers do not require EQF level six in the field of expertise identified in this study. The research confirms the idea that teachers and students from different fields need common expertise in the health- and social care area.